التصميم الأفضلي لمفرّع قدرة ميكروي متعدد المقاطع من المرتبة (n) حاسوبياً - دندة, رضوان (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف البحث إلى تصميم أفضلي, من خلال برنامج حاسوبي, لمفرع قدرة ميكروي من المرتبة n ,مع إجراء التجارب الضرورية لقياس العزل بين الفروع لمفرعة ثلاثية . قياس نسبة الأمواج المستقرة ,و الخواص الترددية, عند اعتباره مكافئاً ثنائي الفروع, الذي فيه الفرع الثالث محمل بدليل موجة ذي ممانعة قدرها 2Z0 . يساعد البرنامج في تحديد الممانعات Z(X), وقيم R(X) على طول النواقل الشرائحية المستخدمة في تنفيذ مفرع قدرة ميكروية, يعمل في المجال (L,S) الترددي الراديوي . The main object of this work is to perform an optimal design of a power microwave divider of n – degree using a computer program, for the measurement of the isolation between three used ports measuring the standing wave ratio,and frequency characteristics considering the microwave divider is equivalent to bi-branch while the third branch is loaded by a wave of characteristic impedance (2zo). This program helps to determine the Z(x) impedance and R (x) along microstrip lines which are used in(L.S) radio frequency band.